PENGARUH PELATIHAN PROFESIONAL, PERTIMBANGAN PASAR KERJA, PENGHARGAAN FINANSIAL, PERSONALITAS TERHADAP MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIER SEBAGAI AUDITOR - Endah Prawesti Ningrum; Lanita Br Hasibuan; Nita Komala Dewi (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2021)
This research is quantitative research. This study aims to determine: (1) Professional Training effect on the Career Selection as an Auditor. (2) Labour Market Considerations effect on the Career Selection as an Auditor. (3) Choice Financial Awards on Career Selections effect on Auditor. (4) The Influence of Personality on Career Selection as an Auditor. The sampling technique is purposive sampling which is one of the techniques in the non-probability sampling group. The data collection method used in this study used the questionnaire method. Prerequisite tests on the data can use the data quality test and the classical assumption test. The data analysis technique used is multiple linear regression analysis, t statistic test (Partial), F test (Simultaneous), and coefficient of determination test (R2). After processing the data, the results showed that: (1) Professional Training had an effect on Career Selection as an Auditor, (2) Labour Market Considerations had an effect on Career Selection as an Auditor, (3) Financial Awards had no effect on Career as an Auditor. (4) Personality has an effect on Career Selection as an Auditor